THE RELATIONSHIP BETWEEN HYPERTENSION AND STROKE IN THE ELDERLY IN TAMAN BODHI ASRI MEDAN: HUBUNGAN HIPERTENSI DENGAN KEJADIAN STROKE PADA LANSIA DI TAMAN BODHI ASRI MEDAN - martina, siska evi; Siregar, Rinco; Sinaga, Janno; Zefanny, Glori Feby (Essential English Grammar, 2025)
Hypertension is one of the factors of stroke. the number of people with hypertension in the elderly is very high. The purpose of the research was determine the relationship between hypertension and the people who get stroke in the elderly at Taman Bodhi Asri Medan, Kecamatan Medan  Sunggal  in 2024. The method of the research was an analytic survey using a cross – sectional design. The population of the research were all hypertension and stroke as many as 46 people. The technique of sampling used by total sampling with 46 elder people who affected by hypertension and stroke. Data was collected by looking at medical records. The statistical test was used by Fisher’s Exact Test. The result of the study obtained in grade 1 of hypertension (140/90 – 159/99 mmHg) were 36 people (78,3), grade 2 of hypertension (160/100 – 179/109) were 10 people (21,7%). There were 17 people (37%) who had a stroke and 29 people (37%) who did not have a stroke. The result obtained by using Fisher’s Exact test showed that the hypertension in grade 2 correlated with stroke’s patients, have 8 people (80%) with p value 0,003 and having an old ratio = 10,106. This is because of hypertension in grade 2 is 10,106 times more possible to get a stroke. It was concluded that the higher of hypertension’s degree,  will get the stroke faster. Therefore, this study is expected that one who with hypertension must be careful. Do not let the degree of hypertension increase because it will be 10.106 times to get a stroke.